(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The annotated article refers to the need of typification of the knowledge used at the initial stage of language acquisition. Reasons for classification in the typology may be different, due to the peculiarities of the central concept interpretation of linguistic typology, which can also mean «language type» and «type in language». In article need of an explication of the acquired grammatical knowledge, classifications of separate levels in one language is staticized, the interpretation of language type – «type in language» is used, and the taxonomical structural characteristic of the simple Russian sentence based on definition of types of the sentences proceeding from essence of the central nodal word – a sentence stemma is given.